2015
DOI: 10.1007/s10143-015-0652-0
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma multiforme in the very elderly

Abstract: Glioblastoma is the most malignant and most common primary brain tumour and is treated with resection followed by post-operative radiotherapy and chemotherapy. However, a significant amount of patients are older than 80 years, and such an approach may not be appropriate. Data on patients aged 80 or older with glioblastoma from two hospitals was collected using the CNS Tumour Database on the Australian Comprehensive Cancer Outcomes and Research Database (ACCORD) system operated by BioGrid. Between 2008 and July… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Moreover, the tolerability of combined radiotherapy and temozolomide seems to be reduced in the elderly [20]. However, other studies have shown that age in itself is not a contraindication to chemotherapy and recent trials for glioblastoma in the elderly have not included a combined radiation and chemotherapy arm [2]. MGMT promoter methyl ation was shown to be a prognostic marker of outcome, and a strong predictor of benefit with temozolomide chemotherapy in elderly patients [4,11,19,21,22].…”
Section: Research Article Pretanvil Salinas and Piccionimentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the tolerability of combined radiotherapy and temozolomide seems to be reduced in the elderly [20]. However, other studies have shown that age in itself is not a contraindication to chemotherapy and recent trials for glioblastoma in the elderly have not included a combined radiation and chemotherapy arm [2]. MGMT promoter methyl ation was shown to be a prognostic marker of outcome, and a strong predictor of benefit with temozolomide chemotherapy in elderly patients [4,11,19,21,22].…”
Section: Research Article Pretanvil Salinas and Piccionimentioning
confidence: 99%
“…Glioblastoma is the most common adult primary malignant brain tumor [1]. The median age at diagnosis is 64 years with a peak incidence in patients aged 75-84 years, numbers which are expected to further increase as the aging population expands [2,3]. Gliomas account for half of all intrinsic brain tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies in neurosurgical patients have used functional status (Karnofsky Performance Status [KPS] < 70) or age (≥ 85 years) to define frailty. 11,49 In the present study, all patients had a KPS of 100 except for 2 patients younger than 80 years with a KPS of 90. Frailty was quantified using the Canadian Study of Health and Aging Modified Frailty Index (mFI).…”
Section: Patientsmentioning
confidence: 44%
“…This is probably the reason why up to 34% of patients do not receive oncological treatment after diagnostic biopsy [19,22]. An even higher number was reported in an Australian study of GBM in patients aged 80 or older, where only 6 out of 40 patients continued with postoperative radiotherapy or chemotherapy [27].…”
Section: Discussionmentioning
confidence: 99%